Association of primary allostatic load mediators and metabolic syndrome (MetS): A systematic review - Osei, Francis; Block, Andrea; Wippert, Pia-Maria (Frontiers in Endocrinology, 2022)
Allostatic load (AL) exposure may cause detrimental effects on the neuroendocrine systems leading to metabolic syndrome (MetS). The primary mediators of AL involve serum dehydroepiandrosterone sulfate (DHEAS; a functional HPA axis antagonist); further, cortisol, urinary norepinephrine (NE) and epinephrine (EPI) excretion levels (assessed within 12-h urine as a golden standard for the evaluation of the HPA axis activity, and sympathetic nervous system activity). However, the evidence of an association between the primary mediators of AL and MetS are limited. This systematic review aimed to critically examine the association between the primary mediators of AL and MetS. PubMed and Web of science were searched for articles from January 2010 to December 2021, published in English language. The search strategy focused on cross-sectional and case-control studies comprising adult participants with MetS, obesity and overweight and without chronic diseases. The STROBE checklist was used to assess study quality control. Out of 770 studies, twenty-one studies with a total sample size (n = 10,666) met the eligibility criteria. Eighteen studies were cross-sectional, and three studies were case-control studies. The included studies had a completeness of reporting score of (COR % = 87.0 ± 6.4%). It is to resume, that cortisol as a primary mediator of AL showed association to MetS in 50% (urinary cortisol), 40% (serum cortisol), 60% (salivary cortisol) and 100% (hair cortisol) of the studies. For DHEAS, it is to conclude that 60% of the studies showed association with MetS. In contrary, urinary EPI and urinary NE both showed 100% no association with MetS. In summary, there is a tendency for the association between higher serum cortisol, salivary cortisol, urinary cortisol, hair cortisol, and lower levels of DHEAS with MetS. Future studies focusing on longitudinal data are warranted for clarification and understanding of the association between the primary mediators of AL and MetS.